Copper‐Catalyzed Trifluoromethylation of Hydrazones Leading to the Formation of Quaternary α‐Trifluoromethyl Diazenes. Issue 6 (29th April 2016) - Prieto, Alexis; Bouyssi, Didier; Monteiro, Nuno
Abstract: The copper‐catalyzed azomethine trifluoromethylation of ketone‐derived hydrazones with Togni′s hypervalent iodine(III)‐CF3 reagent is described. The reaction gives rise to quaternary α‐trifluoromethyl diazenes under mild conditions and is proposed to proceed via a radical process. Abstract : Three and in : The Cu‐catalyzed trifluoromethylation of ketone‐derived hydrazones with Togni hypervalent iodine(III)‐CF3 reagent affords quaternary α‐trifluoromethyl diazo compounds under mild conditions and is proposed to proceed via a Cu I /Cu II redox mechanism.